The Influence of Interorganizational Politics on Acquisition Motives and Acquisition Process - Kivelä, Juha (My University, 2003)
The Influence of Interorganizational Politics on Acquisition Motives and Acquisition Process The focus of the thesis was to research acquisition motives and the influence of interorganizational politics on acquisition motives and acquisition process. The thesis includes research of the relevant literature on acquisition motives, acquisition process, interorganizational politics and distribution of power inside organizations. The focus of the theoretical study was to give background information on the issue at hand. Based on the literature and previous studies, an acquisition model was formed to illustrate the key areas of acquisitions. This model was tested in the empirical study. The theoretical part of the thesis includes relevant literature on the researched area. These include printed material and information in electronic form. The empirical study is based on interviews on persons, which have been involved in acquisitions and on material from Sonera on Sonera Corporation’s acquisitions of iD2 and Across Wireless. The results of the study indicate that the motives for acquisitions are often strategic, but also issues involving politics and power distribution inside corporation influence the motives. These factors are also important in the course of the acquisition process. The outcome of a firm’s acquisition process seems to be a combination of both strategic and non-strategic issues. Furthermore, an important determinant for the whole acquisition process and the influencing factors are sometimes defined before the acquisition motives are set.
Keywords: Acquisition; process; motives; politics; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|